1988
DOI: 10.1093/nar/16.8.3341
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hybrid arrest by tandem antisense oligodeoxyribonucleotides or oligodeoxyribonucleoside methylpbosphonates in a cell-free system

Abstract: Antisense oligonucleotides containing either anionic diester or neutral methylphosphonate internucleoside linkages were prepared by automated synthesis, and were compared for their ability to arrest translation of human dihydrofolate reductase (DHFR) mRNA in a nuclease treated rabbit reticulocyte lysate. In the case of oligodeoxyribonucleotides, tandem targeting of three 14-mers resulted in synergistic and complete selective inhibition of DHFR synthesis at a total oligomer concentration of 25 microM. Hybrid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…The chance of a sequence of 5 bases occurring at random is therefore 45 or 1 in 1024. Since there are approximately 9200-9700 bases in the HIV genome, a given sequence of 5 bases may, on a random basis, occur nine times. Actually a computer search reveals a frequency of occurrence in the HIV genome of all possible tetramers ranging from 0 (CGCG) to 149 (AAAA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chance of a sequence of 5 bases occurring at random is therefore 45 or 1 in 1024. Since there are approximately 9200-9700 bases in the HIV genome, a given sequence of 5 bases may, on a random basis, occur nine times. Actually a computer search reveals a frequency of occurrence in the HIV genome of all possible tetramers ranging from 0 (CGCG) to 149 (AAAA).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligodeoxynucleotides and their analogues have been used as tools for inhibiting viral replication (1-3), for blocking splicing and translation of mRNA (4,5), and for regulating specific gene expression (6,7). It has been found that an oligonucleotide complementary to a segment of a viral genome or an mRNA derived therefrom may interfere with the expression of that genetic segment by hybridization competition (1,2).…”
mentioning
confidence: 99%
“…In particular, by extending the methylphosphonate sequences at each end of the molecule we may enhance cell uptake of the oligodeoxynucleotide in addition to protecting the molecule from exonucleases (Miller et al, 1981). In addition, by reducing the length of the internal phosphodiester sequence we may reduce the target for endonucleolytic degradation while retaining the ability of the molecule to direct ribonuclease-H cleavage of mRNA at the site of hybridisation (Donis-Keller, 1979), an anti-sense mechanism of sequence specific protein synthesis inhibition not exhibited by homogeneous methylphosphonate oligonucleotide analogues (Maher & Dolnick, 1988). We envisage that by reducing the number of phosphodiester linkages to the minimum required for ribonuclease-H activity it may be possible to target a specific site on the mRNA (Shibahara et al, 1987) and hence inhibit expression of a gene carrying a single point mutation at that site, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotides, in the fully protected, trityl-on, controlled pore glass support-bound form, were deprotected following the procedure for methylphosphonate oligonucleotide analogues (Maher & Dolnick, 1988 N-ras anti-sense chimeric oligodeoxynucleotides…”
Section: Synthesis Of Oligodeoxynucleotidesmentioning
confidence: 99%
“…Several modifications, introduced into oligomers to reduce their sensitivity to nucleases, impaired their ability to elicit RNase H activity. This is the case with methylphosphonates (3,4), phosphoramidates (5), 2'-O-alkyl RNA (6) and alpha analogues (4,7,8). Composite oligonucleotides made of differently modified (or unmodified) parts were prepared that aimed at combining different properties within a single molecule (9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%